ANALISIS BUKU AJAR BAHASA ARAB MADRASAH IBTIDAIAYAH KELAS 1 DARI KEMENTRIAN AGAMA REPUBLIK INDONESIA - Sofiah Rosyadi (Jurnal Al-Maqoyis, 2019)
Teaching materials are one of the most important content in teaching and learning activities, which are in the form of materials arranged in textbooks, the right textbook is a book that contains quality material in accordance with the applicable curriculum at that time. The purpose of writing here is to analyze the Arabic language textbook for grade 1 Madrasah Ibtidayyah prepared by the Ministry of Religion (Kementrian Agama) of the Republic of Indonesia, which was published in the first printing in 2020, and gave good category results with a little more initial input on the introduction of hijaiyah letters (Arabic alphabet), their sounds(makhraj) and their writing. The study uses the method of content analysis of the contents of the textbook material with a qualitative approach and describes it descriptively about the suitability of the material with the 2013 curriculum which is seen from the aspects of presentation, content, language, and graphics in the textbook.